Disciplined Teachers are the Key to Quality Education - Ningrum, Anggi Vidya; Waluyo, Heri; Haryati, Lilis; Subandi, Subandi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Teacher discipline is one of the success qualities in the world of education. Disciplined teachers can set a good example for students. Students can develop their knowledge if they have teachers who are disciplined in administration and science. Teachers not only provide information but also help students understand the concept of effective learning. Teachers play a role in shaping students' character and ethics in interacting with other people. Apart from that, teachers also play a role in fostering student independence and confidence. So teachers are one of the internal factors in the quality of education. In this case, teachers must be required to be professional, for example teachers providing creative and innovative learning to encourage students to achieve optimal achievement. Disciplined teachers are also one of the keys to the success of the quality of education in a school.